Resilience and socioeconomic status as predictors of life satisfaction and psychological well-being in colombian older adults (2020)
Well-being is a complex construct related to sociodemographic and cultural aspects that vary across cultures. Latin America is a region with high social inequalities among population groups, although this varies significantly depending on the country. This article proposes a model that seeks to establish the relationship between psychosocial variables, psychological well-being, and life satisfaction in a sample of Colombian older adults. The model explores associations between resilience, socioeconomic status, life satisfaction, and psychological well-being. A study with a sample of 617 Colombian older adults was conducted. A structural equation modeling technique was performed. The results showed a model in which life satisfaction is positively explained by psychological well-being and resilience, whereas psychological well-being is explained by a higher socio-economic status. The results contribute to the evidence about how well-being is determined by psychosocial and cultural factors. The evidence found represents novel information about older adults in Colombia.